2023
DOI: 10.1039/d3bm00805c
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a concentrated growth factor/mesoporous bioactive glass composite scaffold and its application in rabbit mandible defect regeneration

Abstract: Maxillofacial bone defect repair and regeneration remains a tremendous challenge in the field of stomatology. However, the limited osteoinductivity of artificial materials and the high cost of bioactive agents restrain...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…New composites have been developed in recent years which exhibit combined properties of individual components and can adapt to the complex maxillofacial structure. 92–94 These materials can achieve both anti-infectious and osteogenic functions simultaneously. Organic/inorganic complexes are among the most commonly used composite materials for this purpose, providing a promising solution for infectious bone defects in the maxillofacial region.…”
Section: Artificial Biomaterialsmentioning
confidence: 99%
“…New composites have been developed in recent years which exhibit combined properties of individual components and can adapt to the complex maxillofacial structure. 92–94 These materials can achieve both anti-infectious and osteogenic functions simultaneously. Organic/inorganic complexes are among the most commonly used composite materials for this purpose, providing a promising solution for infectious bone defects in the maxillofacial region.…”
Section: Artificial Biomaterialsmentioning
confidence: 99%
“…This fosters an environment conducive to bone regeneration. Additionally, with its unique flowability and injectability, LPCGF can be integrated with other tissue engineering materials. This highlights its remarkable biocompatibility and carrier capabilities. Essentially, the distinctive composition and biological characteristics of LPCGF make it a formidable candidate for a bioscaffold in bone tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…To fabricate bone tissue engineering scaffolds, mesoporous bioactive glass (MBG) has gained much attention due to its abilities of high drug loading and inducing bone-like apatite deposition ( Zhu et al, 2015b ; Feng et al, 2023 ; Yang et al, 2023 ). Furthermore, combining MBG with biodegradable polymers to form composite scaffolds can enhance mechanical strength and regulate biological properties of the scaffolds ( Atkinson et al, 2022 ; Shi et al, 2022 ; Atkinson et al, 2023 ; Ma et al, 2023 ; Sanchez-Salcedo et al, 2023 ). For example, Wu et al demonstrated the enhanced osteogenic ability and mechanical strength by loading dexamethasone into the 3D printed MBG scaffolds with poly(vinyl alcohol) as a binder ( Wu et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%